Analisis Peristiwa Alih Kode dan Campur Kode pada Novel Negeri 5 Menara Karya Ahmad Fuadi - El Farouq, Muhammad Ayyinna Yusron (University of Brawijaya, 2019)
This study aims to find events in code switching and code mixing in dialogues between leaders in Negeri 5 Menara's novel by Ahmad Fuadi. The research data is in the form of words, phrases, clauses, and sentences. This type of research is descriptive qualitative with a sociocultural approach. Data collection techniques are document analysis Data were analyzed by descriptive analysis techniques. The analysis technique is done by taking enough data that is considered to represent the whole of the data. Based on the results of the analysis, it was found that there were 58 interfering code events and 18 code switching speech events. Symptoms of code switching are intertwined in four different languages that involve the use of Batak, Minang, Arabic, English, and France languange. The occurrence of code switching relates to the speaker and the speaker, the speech partner, the function and purpose of the conversation, and the conversation situation. The code interfering factor is extralinguistic and intralinguistic factors.